Excessive Weight Gain During Pregnancy Increased Ponoxarase 1 Level in Neonatal Cord Blood - Serhat Ege; Hasan Akduman; Ayşegül Aşır; Tuğcan Korak (Antioxidants)
Maternal obesity is increasingly recognized as a risk factor for adverse fetal outcomes, primarily through its association with heightened oxidative stress. This study aimed to evaluate oxidative stress markers in umbilical cord blood of neonates born to obese mothers. Sixty-three pregnant women, who were of normal weight at the start of pregnancy but classified as obese at term, were included. Umbilical cord blood samples were collected immediately post-delivery and analyzed for serum oxidative stress markers (total oxidant status (TOS), total antioxidant status (TAS), paraoxanase (PON), aryl esterase, thiol, and catalase activities). Protein interaction networks were generated using Cytoscape (v3.10.3), and the overlapping proteins were further analyzed for functional annotations with ShinyGO (0.80). The top ten significantly enriched pathways were identified with a false discovery rate (FDR) threshold of <0.05. Significant associations were found between maternal BMI change and paraoxonase 1 (PON1) levels in umbilical cord blood, while no correlation was observed with other oxidative (total oxidant status) and antioxidant markers (total antioxidant status, aryl esterase, thiol, and catalase). Additionally, the correlation analysis showed a significant relationship between BMI change and fetal gestational age, but not with other demographic or clinical features. A total of 24 common protein interactors associated with PON1, obesity, and oxidative stress were identified. Functional annotation analysis revealed significant enrichment in antioxidant and oxidoreductase activities, along with pathways involved in insulin resistance, AGE-RAGE signaling, and atherosclerosis. Maternal obesity may specifically affect PON1 activity, potentially serving as a compensatory response to oxidative stress in neonates, suggesting PON1 as a possible biomarker for oxidative stress-related metabolic disturbances in neonates of obese mothers, with implications for monitoring and managing pregnancy outcomes in obese populations.